Survey on Actual Situation of Small Springs - Committee for Small Springs, Research (Transaction of Japan Society of Spring Engineers, 1998)
This report deals with the results of survey on the actual situation of springs and the proposal of future research subjects for spring technology at the request of Japan Spring Manufacturers Association. Firstly, this committee investigated the index of literature of small springs from Transaction of Japan Society for Spring Research, and collected the manufacturing data of small springs in Japanese industries. Secondly, the committee analyzed the index of literature and data collected under the title of the above mentioned purposes, and classified them into three categories of design, material and manufacture. In conclusion, this committee is reguested to propose the main research subjects of small springs to be chosen in future for Japan Society for Spring Research.